2005
DOI: 10.1103/physrevlett.95.087801
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Torque and Orientation Dynamics of Liquid Crystals with Dielectric Dispersion

Abstract: We demonstrate that the finite rate of dielectric relaxation in liquid crystals which has been ignored previously causes profound effects in the fast dielectric reorientation of the director. We propose a theory of dielectric response in which the electric displacement depends not only on the present (as in the standard theory) but also on the past values of electric field and director. We design an experiment with a dual-frequency nematic in which the standard "instantaneous" model and our model predict effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(59 citation statements)
references
References 11 publications
1
58
0
Order By: Relevance
“…The extracted proteins were digested in a trypsin solution at 37°C for 16 h. Afterwards, the peptides extraction was done with a solution of 50% acetonitrile and 5% formic acid (Yin et al 2005). The solution containing the proteolytic digests was first fractionated in a ionic exchange column.…”
Section: Mass Spectrometry Analysismentioning
confidence: 99%
“…The extracted proteins were digested in a trypsin solution at 37°C for 16 h. Afterwards, the peptides extraction was done with a solution of 50% acetonitrile and 5% formic acid (Yin et al 2005). The solution containing the proteolytic digests was first fractionated in a ionic exchange column.…”
Section: Mass Spectrometry Analysismentioning
confidence: 99%
“…Then a s ðt; t 0 Þ can be described in the laboratory frame by the diagonal components a k ðt À t 0 Þ alongn and a ? ðt À t 0 Þ perpendicular ton [21,23]: a s ðt; t 0 Þ ¼ a k ðt À t 0 ÞnðtÞ#nðt 0 Þ þ a ? ðt À t 0 ÞÎðtÞ#Îðt 0 Þ n þmðt 0 Þ#mðt 0 Þg;…”
Section: Dielectric Memory Effect: An Outline Of the Theorymentioning
confidence: 99%
“…According to the dielectric spectroscopy data [19,20], this switching time is in fact of the same order as t for 5CB, which might suggest that the NLC response is influenced by the dipole relaxation dynamics. Direct evidence came first from the experiments with DFNs [21,22], in which t is long, and thus easier to study. It was demonstrated that when the electric field changes over the time close to t, the instantaneous and 'past' contributions to the dielectric torque can indeed be comparable; moreover, they can cause opposite directions of the director reorientation [21,22].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations